GERAKAN SOSIAL ISLAM: Kemunculan, Eskalasi, Pembentukan Blok Politik dan Tipologi Artikulasi Gerakan - Jurdi, Syarifuddin (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2013)
Islamic social movement was a unique phenomenon during the 20th century. This movement was then transformed into certain orientation to purify Islamic values. The emergence of Islamic social movement in several countries was a response to internal and external condition of Muslims all over the world, with particular attention to colonialism and imperialism which were developed by Western countries against Islamic world. In general, Islamic social movement emerged in order to attract emancipation and transformation of Muslim communities and to rearrange socio-political and economical identity of Muslim communities in order to be in line with Islamic ethical values.